KEEFEKTIFAN LAYANAN BIMBINGAN DAN KONSELING PADA MASA COVID-19 DI KELAS X MAN 2 PONTIANAK - Kukuh Wijayanto; Indri Astuti; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe world was shocked by the outbreak of the Corona virus or Covid-19 whichinfects almost all countries in the world. Covid-19 is transmitted through directcontact with the respiratory tract of an infected person. One of the methods usedin Indonesia is a PPKM. One of the impacts of PPKM is online learning. Ofcourse, online learning or learning (online) also affects other teachers,especially Guidance and Counseling teachers. Professional Guidance andCounseling teachers must be able to solve student problems, and provideGuidance and Counseling services that help students optimize their abilities andrelax the problems they face. The purpose of this research is to obtain data andinformation about the effectiveness of the guidance and counseling servicesprovided by the Guidance and Counseling Teacher grade X MAN 2 Pontianak.The effectiveness of Guidance and Counseling Teachers in improving theguidance and counseling services provided grade X students of MAN 2Pontianak by providing question and answer sessions, students to choose theirown process of guidance and counseling services to be provided, adjusting thetheme of guidance and counseling services to the things that students areinterested in, appreciate the good thoughts and opinions of students.Keywords: COVID-19, Effectivity, Guidance and Counseling.